Design of coplanar waveguide band‐pass filter for S‐band application. Issue 3 (25th March 2015) - Mondal, Pratik; Ghosh, Amit; Parui, Susanta Kumar
Abstract : Coplanar waveguide (CPW) has a huge demand for designing band‐pass filter (BPF). In this study, the filter designed by open‐ended CPW series stub which acts as a resonant circuit thus giving a band‐pass response. As the number of open stub discontinuity is increased, the frequency response and roll‐off rate of the proposed BPF has improved gradually. Electromagnetic simulated and measured results show a very good agreement with each other. The proposed filter is designed to obtain a frequency range of 1.97–4 GHz (S‐band) having rising edge and falling edge selectivities of 35.9 and 45.7 dB/GHz, respectively.